DETERMINANTS OF THE CO-CREATION OF CONSUMER VALUE ON THE SPORTS EVENT MARKET - Zygmunt Waśkowski (Polityki Europejskie, Finanse i Marketing)
Although the concept of the co-creation of consumer value has been subject to numerous research projects and scientific debates, it still arouses controversy. Its possible applications are still discussed and its various aspects require more in-depth analyses. This article is conceptual in nature and presents the determinants of the co-creation of value on the sports event market. It also addresses its opportunities and limitations. The conducted analysis allowed for a conclusion that the creation of value for sports events is cooperative in nature, with three main groups of entities involved.